The viewpoint of nanolipid vesicles (liposomes, exosomes, and microvesicles) as biosensors in medical health advances - Ghazizadeh, Elham; Nasery, Zahra (Frontiers in Nanotechnology, 2023)
Since biosensors are of great importance today in the rapid, sensitive, and reliable detection of biological molecules in many fields, including medicine, the development of a strong and reliable diagnostic agent is a very interesting topic. Because of their unique features, among other nanomaterials, lipid-based vesicles as liposomes, exosomes, microvesicle represent a type of biocompatible and versatile biosensing membrane surface for rapid biomarker detection and diagnosis of diseases to enhance the assay sensitivity and decrease the detection limit. In this review, we have reviewed the recent diagnostic application of lipid-based vesicles as biosensing substances in both conventional and novel techniques for identifying targets, especially in medicine and biotechnology sciences. Eventually, we have highlighted several recent promising developments in a new generation of biosensors based on liposome-nanomaterial hybrids and exosomes for analyzing targets and possible further advances in the future.